2004
DOI: 10.1113/jphysiol.2004.071548
|View full text |Cite
|
Sign up to set email alerts
|

Transcellular thiocyanate transport by human airway epithelia

Abstract: Human airway mucosa synthesizes and secretes lactoperoxidase (LPO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 33 publications
5
93
0
2
Order By: Relevance
“…Since previous studies showed that CFTR played a role in SCN À transport from the serosal to mucosal compartments [17], we evaluated the possible contribution of CFTR anion channel activity to the SCN À transport observed in cultures. Non-CF cultures showed the expected increase in SCN À transport after stimulation of PKA by apical addition of dibutyryl cAMP (0.5 mM) and forskolin (10 lM), while CF cultures did not (Fig.…”
Section: Thiocyanate Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…Since previous studies showed that CFTR played a role in SCN À transport from the serosal to mucosal compartments [17], we evaluated the possible contribution of CFTR anion channel activity to the SCN À transport observed in cultures. Non-CF cultures showed the expected increase in SCN À transport after stimulation of PKA by apical addition of dibutyryl cAMP (0.5 mM) and forskolin (10 lM), while CF cultures did not (Fig.…”
Section: Thiocyanate Transportmentioning
confidence: 99%
“…We have previously shown that normal human bronchial epithelial cells actively transport SCN À from the basolateral to apical surfaces and that the transport was regulated by CFTR as it was stimulated by cAMP analogs and by forskolin, and inhibited by apical glibenclamide, diphenylamine-2-carboxylic acid and 5-nitro-2-(3-phenylpropylamino)-benzoate [17]. Since a loss of SCN À in the airway lumen might result in a loss of LPO antibacterial activity and perhaps also affect neutrophil MPO antibacterial activity, we assessed whether SCN À transport was defective in CF bronchial epithelial cells compared to normal epithelia.…”
Section: Thiocyanate Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…(40), providing oxidants to support the lactoperoxidase-H 2 O 2 -thiocyanate antimicrobial system (41,42). Defective thiocyanate transport in cystic fibrosis subverts optimal activity of this system and contributes in part to the frequent respiratory infections seen in patients with this disorder.…”
Section: Nox3-p22mentioning
confidence: 99%
“…Moreover, recent studies have shown that iodide may play an important role in the innate immune system of the pulmonary tree by acting as a substrate for an oxidative microbicidal system [6,7]. Iodine accumulation in bronchopulmonary secretions, while acting to defend against respiratory viruses and bacteria in inflammatory lung states [6][7][8][9][10], may also lead to false-positive post-RAI scans resulting in erroneous diagnoses.…”
mentioning
confidence: 99%